Planning through information sharing across a supply chain - Buakaew, Athitaporn; Masuchun, Ruedee (My University, 2008)
This paper presents a linear integer programming model to plan the production through information sharing across a supply chain. The advantage is that information sharing makes the whole supply chain globally visualized and yet decreasing in variability on the supply chain. Instead of individually plan for its own manufacturing, demand from all retailers are accumulated and then globally planned for all manufacturers. The objective function of the proposed model is to minimize the total costs involved. Numerical results verify that this model can be used to generate feasible and optimal plans across the supply chain. © 2008 SICE.
Keywords: Supply chain management